Effect of the Pilates Method on Sexual Function, Pelvic floor Muscle Strength and Quality of Life of Breast Cancer Survivors - de Souza Ferraz, Vanessa (2020)
Introduction: Surgical treatment of breast cancer and anti-estrogenic hormone therapy negatively impact quality of life and female sexual function. Considering that physical activity provides important benefits to minimize the physical and emotional impact of the treatment, the Pilates Method is a modality of physical exercises that could increase the quality of life parameters of women survivors of breast cancer. Objective: To study the impact of Pilates Method on pelvic floor muscle (PFMS) strength, sexual function (SF), and health related quality of life related (HRQL) of BC survivors. Method: Randomized clinical trial in which 24 mastectomized women were divided into two groups: Pilates (G1) and control group (G2) exercises for 8 weeks. SF was assessed by the FSFI questionnaire and HRQV by the EORTC QLQ-C30 questionnaire. PFMS was assessed by perineometry and contractility using the PERFECT scheme. Values are expressed as mean ± standard deviation. Inferential analysis was performed using repeated measures ANOVA and Bonferroni post-test. Results: Women of the G1 showed better performance than those of the G2 for the following variables: sexual function, degree of muscle contraction; all items of the PERFECT scheme; QLQ-C30 questionnaire domains: global health status, physical functioning, emotional functioning; symptom scale items fatigue, nausea, and pain, and perception of financial difficulties (p < 0.05). Conclusion: The results show benefits of supervised Pilates exercises on pelvic floor muscle contractility, sexual function, and quality of life after cancer.